The Utilization of the "Tsutaeru Hatsuon" Online Media in Learning Japanese Accents and Intonations - Heni Hernawati; Dwi Puji Asrini (IZUMI, 2021)
This study reveals the analysis of the online media's role, "Tsutaeru Hatsuon", to improve Japanese language learners in mastering and to apply Japanese phonetics, especially in accents and intonation. This study uses primary data in the form of respondents' answers to questions in the website "Tsutaeru Hatsuon", which was conducted twice, namely pre-test and post-test, and secondary data in the form of responses questionnaires. Respondents in this study were 64 Japanese language education students at Semarang State University, class of 2019. The results showed that the post-test scores increased than the pre-test scores. In Japanese intonation material, respondents who answered questions correctly on all questions increased by 23%, while in accent material, respondents who answered questions correctly on all questions increased by 31%. Thus, it can be concluded that there is an improvement in the respondent's ability to understand Japanese intonation and accent after using the "Tsutaeru Hatsuon" website. According to respondents, the questionnaire answers showed that the website "Tsutaeru Hatsuon" is easy to understand and use. Moreover, the material is easy to understand, and the explanation is very detailed, which is equipped with sound files and learning videos. It is beneficial for learners to be able to understand Japanese accents and intonations directly.